2020
DOI: 10.1111/emre.12421
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management and Organisational Performance: The Mediating Role of Social Exchange

Abstract: This study seeks to explore the impact of specific set of HRM practice on organisational performance in a Middle Eastern emerging market. It aims to examine the mediating role of social exchange within the healthcare sector in Jordan, which is presently reeling under pressure from the refugee crisis from Syria and neighbouring countries. Both, HR and hospital managers were targeted in all private and public hospitals through two separate questionnaires. We find, as predicted, that recruitment, training, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 69 publications
3
33
0
3
Order By: Relevance
“…According to the organizational support theory, which is rooted in SET, employees will perform their tasks and reciprocate in a similar fashion to the way they have been treated (Jabutay and Rungruang, 2021;Mohammad et al, 2021)…”
Section: Performance Appraisal Affective Commitment and Iwbmentioning
confidence: 99%
“…According to the organizational support theory, which is rooted in SET, employees will perform their tasks and reciprocate in a similar fashion to the way they have been treated (Jabutay and Rungruang, 2021;Mohammad et al, 2021)…”
Section: Performance Appraisal Affective Commitment and Iwbmentioning
confidence: 99%
“…Untuk itu, demi mewujudkan SDM yang unggul diperlukan adanya manajemen sumber daya manusia yang tepat untuk mengelola dan mengembangkan SDM di sektor pelayanan kesehatan. Manajemen sumber daya manusia memprioritaskan SDM sebagai salah sumber daya yang harus dikelola secara efektif (Mohammad et al, 2021), hal tersebut mengingat bahwa dengan adaya manajemen sumber daya manusia yang tepat dapat membantu organisasi manapun dalam mencapai kinerja yang unggul dan berkelanjutan (Verburg, 2014).…”
Section: Hasil Dan Pembahasanunclassified
“…Biasanya, setelah membuka rekrutmen karyawan baru, kemudian akan dilanjutkan ke tahap seleksi terhadap berkas-berkas kandidat yang masuk (Verburg, 2014). Proses rekrumen dan seleksi karyawan baru harus dilakukan dengan matang dan sesuai karena keputusan yang diambil akan berpengaruh terhadap kualitas karyawan dan keberhasilan organisasi kedepannya (Mohammad et al, 2021;Phillips & Gully, 2015). Setelah proses rekrutmen dan seleksi selesai, maka perusahaan perlu untuk menempatkan karyawan baru dengan mempertimbangkan posisi pekerjaan yang sesuai dengan kemampuan masing-masing karyawan agar karyawan dapat melaksanakan pekerjaan dengan baik (Sarinah et al, 2017).…”
Section: Grafik 2 Perencanaan Sumber Daya Manusiaunclassified
See 1 more Smart Citation
“…The role of Human Resource Management (HRM) has received great attention in literature for its outcomes on individuals (Miao et al , 2020; Pak et al , 2019; Chang and Chen, 2011) and organizational outcomes (Darwish et al , 2016; Lu et al , 2015; Guerrero and Barraud-Didier, 2004). While majority of the studies have shown positive impact on firm performance (Mohammad et al , 2020; Akoi and Yesiltas, 2020), others have failed to explore any significant relationships (Cappelli and Neumark, 2001; Guest et al , 2003).…”
Section: Introductionmentioning
confidence: 99%